P03.10.B A successful case of Histiocytic sarcoma. (5th September 2022) - Bonzano, E; Colombo, S; Mantovani, L; Di Liberto, R; Filippi, A
Abstract: Background: Histiocytic sarcoma (HS) is an extremely rare malignant neoplasm accounting for less than 1% of all hemato-lymphoid neoplasms. Sixty percent of all cases are metastatic at presentation and the prognosis is really poor. Currently, there are limited treatment options for HS, and no standard treatment can be recommended. Surgery and/or chemotherapy are the most commonly employed treatment modalities for HS, while radiotherapy seems to be an effective option in patients with localized lesions. Material and Methods: A 48-year-old woman admitted to our hospital for a drug-resistant neck pain. Her medical record review was relevant for hypothyroidism in replacement therapy, hystero-adnexectomy for fibromatosis (2 years ago), anxiety-depressive syndrome. A Brain and Head-and-Neck Magnetic Resonance Imaging (MRI) showed a left expansive osteolytic occipito-cervical vertebral lesion at level C1-C2, measuring 3.4cm x 2.3 cm x 2.6 cm. The mass was completely resected on July 12, 2021 and pathological and immunohistochemical staining confirmed the diagnosis of HS with positive immunohistochemistry for CD163, CD4, CD68, CD14, CD45 / LCA; weak expression of S100 and focal positivity for lysozyme; Ki67 = 45%.On August 10, 2021 a 18F-FDG PET/CT imaging of the total body did not reveal any distal metastases. On August 13, 2021 a bone marrow aspirate showed no neoplastic cells. She underwent to an adjuvant chemotherapy regimen that consisted of ifosfamide administered as an infusion with bolus carboplatin, and etoposide (ICE). On August 28, 2021 a concomitant radiotherapy is given, with a total dose of 45 Gy delivered in 15 fractions plus a sequential boost to 54 Gy.Results: VMAT was used to deliver a conformal RT plan. The patient tolerated the entire treatment very well, with a Grade 1 dysphagia immediately after the completion of radiotherapy, with a complete resolution about a week later. At last Brain Head-and-Neck RMN and 18F-FDG PET/CT on March 28, 2022 there is no evidence of recurrent disease. Conclusion: The favorable outcome of our patient with combined chemotherapy and radiotherapy should promote future research to explore treatment protocols in patients with localized or favorable subtypes of HS.For patients with a good PS, young age, long life expectancy, advanced RT techniques may be used to customize safe treatment.